Fossil bat assemblages as palaeoenvironmental and palaeoclimatic indicators : A case study in the Lower to Middle Pleistocene Gran Dolina sequence of Sierra de Atapuerca, Northern Spain - Galán, Julia (2020)
Bat remains occur in low numbers in Pleistocene cave assemblages compared to other small vertebrates, and therefore are rarely used as palaeoenvironmental or palaeoclimatic indicators. In this study we address the correlation between bat palaeocommunity dynamics and climate and environmental factors by analysing the fossil bat record throughout the Lower to Middle Pleistocene Gran Dolina sequence of Atapuerca, Spain. We show that the palaeodiversity and palaeoclimatic markers employed in our bats-based approach provide coherent results with other palaeoclimatic indicators. We report a general impoverishment of bat palaeocommunities towards the upper section of the sequence that correlates with evidence of climate deterioration based on palynological analysis and data from other small vertebrates groups. We also find that the occupational pattern of the dominant bat species Myotis myotis changes at the top of the sequence, from a probable all-year occupation to a seasonal, winter use of the cave, which could be related to the onset of human occupation of the cave-site. Finally, we note that while the Habitat Weighting analysis of bat assemblages is correlated to independent palaeoenvironmental proxies, such bats-based approaches show an overrepresentation of woodland habitats in comparison to other small vertebrates indicators.